Exploration of Ethnomathematics in Roro Ngigel Dance: Representation of Motion and Pattern in Mathematics - Vemas Dwi Agustino; Isna Farahsanti; Eka Prasetyaningsih (Absis: Mathematics Education Journal, 2025)
The purpose of this research is to express the representation of movements and patterns in Roro Ngigel dance in mathematics. The method used in this research is a qualitative method with an ethnographic approach. The instrument in this research is the researcher himself and cannot be represented. The data analysis technique was carried out by determining the geometry domain which was then described. The results obtained in this study are that there is ethnomathematics in the Roro Ngigel dance in the form of angles, lines, translations, and reflections. This research has implications in learning mathematics for learning through the development of mathematical skills, contextual learning, and cultural development or preservation. This can be done with learning strategies such as PjBL, PBL, or Inkuri Learning. The conclusion was obtained ethnomathematics in motion and pattern.